1995
DOI: 10.1111/j.1432-2277.1995.tb01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing and quantification of bone loss in cardiac transplant recipients

Abstract: To evaluate osteopenic bone disease in heart transplant patients, we prospectively measured bone mineral density (BMD) in 33 consecutive male recipients before hospital discharge and 1 year later, using dual photon absorptiometry. At hospital discharge BMD measurement at the lumbar spine was 90% of that expected in healthy age- and sex-matched controls (p = 0.005). One year later BMD had further decreased by 8.5% at the lumber spine and by 10.4% at the femoral neck (P = 0.0001). Five patients suffered vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 18 publications
(12 reference statements)
3
15
0
Order By: Relevance
“…The nonsignificant change in BMD after transplantation is in contrast to previous studies. In most studies, BMD decreased significantly during the first year after transplantation [2,5,6,18,19]. Vertebral fractures are reported to occur at a rate of 21-36% within the first year post-transplant [6,18,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The nonsignificant change in BMD after transplantation is in contrast to previous studies. In most studies, BMD decreased significantly during the first year after transplantation [2,5,6,18,19]. Vertebral fractures are reported to occur at a rate of 21-36% within the first year post-transplant [6,18,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…1). (1,6,7,9,11,12,14,15) A high incidence of fractures, between 20% and 40% in most studies, has also been documented. Fractures commonly affect the spine, ribs, and long bones and may occur very early after transplantation, sometimes within the first month.…”
Section: Clinical Features Of Transplantation Osteoporosismentioning
confidence: 99%
“…(1,2) The critical time for the occurrence of vertebral fractures, however, is the early post-transplantation period, (3)(4)(5) when patients receive high doses of immunosuppressive drugs. (3,4,(6)(7)(8)(9) Prospective studies after CTP reported incidence rates of vertebral fractures between 15% and 36%. (5,8,10,11) In view of this high fracture rate, an effective preventive strategy is warranted.…”
Section: Introductionmentioning
confidence: 99%